Identifying people at higher risk of melanoma across the U.K.: a primary‐care‐based electronic survey. (23rd December 2016) - Usher‐Smith, J.A.; Kassianos, A.P.; Emery, J.D.; Abel, G.A.; Teoh, Z.; Hall, S.; Neal, R.D.; Murchie, P.; Walter, F.M.
Summary: Background: Melanoma incidence is rising rapidly worldwide among white populations. Defining higher‐risk populations using risk prediction models may help targeted screening and early detection approaches. Objectives: To assess the feasibility of identifying people at higher risk of melanoma using the Williams self‐assessed clinical risk estimation model in U.K. primary care. Methods: We recruited participants from the waiting rooms of 22 general practices covering a total population of > 240 000 in three U.K. regions: Eastern England, North East Scotland and North Wales. Participants completed an electronic questionnaire using tablet computers. The main outcome was the mean melanoma risk score using the Williams melanoma risk model. Results: Of 9004 people approached, 7742 (86%) completed the electronic questionnaire. The mean melanoma risk score for the 7566 eligible participants was 17·15 ± 8·51, with small regional differences [lower in England compared with Scotland ( P = 0·001) and Wales ( P < 0·001), mainly due to greater freckling and childhood sunburn among Scottish and Welsh participants]. After weighting to the age and sex distribution, different potential cut‐offs would allow between 4% and 20% of the population to be identified as higher risk, and those groups would contain 30% and 60%, respectively of those likely to develop melanoma. Conclusions: Collecting data on the melanoma risk profile of the general population in U.K. primary care is both feasible and acceptable for patients in a general practice setting, and provides opportunities for new methods of real‐time risk assessment and risk stratified cancer interventions. Abstract : What's already known about this topic? Programmes to identify people at higher risk of melanoma and offer them preventive advice about sun protection, skin awareness, early consultation or surveillance are of increasing interest to healthcare providers in the U.K. and internationally. Numerous models exist for predicting future risk of melanoma, with little difference between models suitable for self‐assessment and those requiring a healthcare professional; none has been calibrated for the U.K. population. What does this study add? Collecting data on the melanoma risk profile of the general population in U.K. primary care is both feasible and acceptable. This provides an opportunity for new methods of real‐time risk assessment in primary care. Using the Williams model produces a distribution of risk in the population attending general practices that allows identification of subgroups at different levels of risk. As regional differences were small, a single approach could be implemented. Plain language summary available online